ChemInform Abstract: Pahangensin A and B, Two New Antibacterial Diterpenes from the Rhizomes of Alpinia pahangensis Ridley. Issue 14 (8th April 2014) - Sivasothy, Yasodha; Ibrahim, Halijah; Paliany, Audra Shaleena; Alias, Siti Aisyah; Awang, Khalijah
Abstract isolation, structure elucidation and antibacterial activity